Phytochemical characterization of bioactive compounds on methanolic and ethanolic leaf extracts of Myrciaria sp. (Scientia Agropecuaria, 2016)
Among the native species of importance in Brazil, jabuticabeira (Myrciaria sp.) is a native fruit tree from several Brazilian regions. Few studies report the chemical constituents of the leaves and its pharmacological and nutraceutical properties. The aim of this study was to identify the phenolic compounds of the methanolic (MeOH) and ethanolic (EtOH) leaf extracts of Myrciaria sp. Phytochemical profile of the extracts was carried-out using High Performance Liquid Chromatography (HPLC) analysis. Antioxidant potential was evaluated by radical scavenging capacity with 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and total phenolics were determined with Folin-Ciocalteau reagent. A total of nine different compounds were identified in the free and bound phenolics extractions: 2,4 dihydroxybenzoic, vanillin, p-coumaric, ferulic, sinapinic, rutin, epicatechin, trans-caffeic and myricetin. The extracts demonstrated high radical scavenging capacity (MeOH: 1.83 and EtOH: 8.05 mg/mL) and high phenolic content (MeOH: 1.15; and EtOH: 1.04 mg/g dry matter). The wide variability of compounds revealed and the amount of peaks not identified, gives us a background of a potential plant matrix for further investigations in order to develop a nutraceutical agent.
Keywords: Myrciaria sp; phenolic compounds; chemical profile; antioxidant capacity